Accurate measurement of long range proton–carbon scalar coupling constants. Issue 4 (16th January 2017) - Dickson, Claire L.; Blundell, Charles D.; Butts, Craig P.; Felton, Alice; Jeffreys, Alex; Takacs, Zoltan
Abstract : The accuracy and ease-of-use of various experimental NMR methods for measuring n J CH values is assessed. Abstract : The accuracy and practicality of measuring heteronuclear scalar coupling constants, n J CH, from modern NMR experimental methods is examined, based on F1 or F2 evolution of n J CH in HSQMBC (including EXSIDE) and HMBC experiments. The results from these methods are compared to both robust experimental data (derived from coupled 13 C spectra), computed (Density Functional Theory) and literature values where available. We report on the accuracy, ease of use and time efficiency of these multi-dimensional methods and highlight their extent and limitations.